Occupational well-being and stress among early childhood professionals: the use of an innovative strategy to measure stress reactivity in the workplace. Issue 1 (1st January 2016) - Nislin, M.; Sajaniemi, N.; Sims, M.; Suhonen, E.; Maldonado, E. F.; Hyttinen, S.; Hirvonen, A.
ABSTRACT: The aim of this study was to examine early childhood professionals' (ECPs) work engagement, burnout and stress regulation in integrated special day-care groups. The participants consisted of 89 ECPs from 21 integrated special day-care groups in Helsinki, Finland. ECPs' work-related well-being was assessed using self-report questionnaires that measured work engagement and burnout. Stress regulation was assessed by measuring salivary cortisol and alpha-amylase activity during consecutive working and weekend day with a total five samples per day. The results indicated that ECPs experienced high levels of work engagement, and even though signs of burnout appeared among ECPs, compared to reference values in general population results showed ECPs generally experienced lower levels of stress. On average ECP's stress regulation was regular, and there were no differences in salivary AA/Cortisol or Cortisol/AA ratios between the working day and weekend day. No connections between stress regulation, work engagement and burnout were found. However, we found associations between ECPs' characteristics and work engagement and burnout; younger ECPs showed lower professional self-esteem and ECPs with higher level qualifications (e.g. special teachers) were more likely to report higher levels of work engagement. The main findings drawn from the data are discussed, and suggestions for future research are provided.